HAK KEKAYAAN INTELEKTUAL ATAS TERCIPTANYA KARYA HASIL ARTIFICIAL INTELLIGENCE (AI) DI TINJAU DARI SEGI SEJARAH DAN IMPLIKASI TERHADAP HUKUM - Susilo, Joko; Mubarrak, Muhammad Zaki (Esensi Hukum, 2024)
The purpose of this writing is to provide a view that with the rapid development of technology, it certainly makes new dynamics related to Intellectual Property Rights produced by Artificial Intelligence (AI) against the current law, which in fact has not been able to accommodate the development of AI technology. the author's research method is the historical method. That the historical method is a method by examining events that have occurred in the past, starting from the stages of heuristics, criticism, interpretation, and historiography. Intellectual property should have existed for a long time, namely in ancient China. At that time, Intellectual Property was in the form of patents given to silk craftsmen specifically for the kingdom. For this performance, the kingdom then gave the title to the craftsman, namely the title of the king's vassal. That the development of Intellectual Property is growing with the times, until the emergence of AI. The emergence of AI is not matched by existing regulations, so it is necessary to immediately formulate these regulations by policy makers.